Stealth Peptides Target Cellular Powerhouses to Fight Rare and Common Age-Related Diseases - Szeto, Hazel H. (Protein and Peptide Letters, 2018)
Background: Mitochondria are the primary source of energy in most tissues. Mitochondrial dysfunction results in cellular energy deficiency, triggers the production of reactive oxygen species, and initiates various cell death and inflammatory pathways. Several cell-permeable peptides (SS peptides) have been described that selectively target cardiolipin on the inner mitochondrial membrane and promote efficiency of the electron transport chain to produce more ATP. Conclusion: In preclinical disease models, these peptides have been shown to repair damaged mitochondria and promote cellular repair and restore function. By mitigating cell injury, these peptides prevent inflammatory responses that can result in chronic inflammation and tissue remodeling. This peptide technology platform represents a paradigm shift in targeting the fundamental cause of cellular energy failure for age-related degenerative diseases.
Keywords: reactive oxygen species